1997
DOI: 10.1177/104063879700900102
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the use of Virus and Antibody Detection Techniques for the Diagnosis of La Piedad Michoacan Paramyxovirus (LPMV) Infection in Pigs

Abstract: Abstract. La Piedad Michoacan paramyxovirus (LPMV) is newly recognized paramyxovirus that has been associated with neurologic and reproductive disorders in pigs in Mexico. To date, no comparative study of methods for the diagnosis of infection with this virus has been published. In this study, we identified tissues containing maximum virus load to optimize virus isolation procedures, and we compared this method to a rapid diagnostic test employing immunostaining of impression smears for LPMV antigens. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…8 The results showed that all 4 tests gave satisfactory results. However, these tests have the following disadvantages.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…8 The results showed that all 4 tests gave satisfactory results. However, these tests have the following disadvantages.…”
Section: Discussionmentioning
confidence: 59%
“…The results presented in Table 2 concerning the experimentally infected boars in Mexico show that all 3 boars were positive on the b-ELISA on day 9, i.e., in agreement with the results of the previous experiment. 8 Field sera from Mexico. All 597 field sera from Mexico were tested by b-ELISA: 431 were positive, and 166 were negative.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations